Constructing and Validating Students’ Psychological Contract Violation Scale - Itzkovich, Yariv (Frontiers in Psychology, 2021)
For two and a half decades, psychological contracts are researched mainly in work organisations as drivers of the attitudes and behaviours of employees, overlooking the importance of understanding the nature of the psychological contracts of students in higher education. This study constructs and validates a new scale for measuring the perceived psychological contract violations of students in the context of faculty incivility. A mixed-method approach was applied to study the issue in three phases. First, a qualitative method was used to capture and analyse the perceived entitlements of students, as described by 78 college students, resulting in 37 items or elements identified by students as reflecting their psychological contracts. Second, a sample of 244 students was studied to identify the perceptions of violated expectations of students. In the final phase, items were rephrased as expectations and were given to the third sample of 154 undergraduate college students to determine the level of fulfilment of these expectations. Additionally, to ascertain discriminate and convergent validity measures, students were asked about the extent to which they experienced faculty incivility (discriminant validity) and frustration with the quality of interaction with their faculty (convergent validity). From these results, students’ psychological contract violation scale was constructed and validated.